What the curtains do not shield: A phenomenological exploration of patient-witnessed resuscitation in hospital. Part 1: patients' experiences - Fiori, M.; Latour, Jos; Endacott, R.; Cutello, C.A.; Coombs, M. (WILEY, 2022)
Aims: The aim of the study was to explore the experiences of hospital patients who witnessed resuscitation of a fellow patient. Design: Descriptive phenomenology. Methods: Patients who witnessed resuscitation were recruited from nine clinical wards in a university hospital in England. Data were collected through face-to-face individual interviews. Participants were interviewed twice,in 1 week and 4 to 6 weeks after the resuscitation event. Data were collected between August 2018 and March 2019. Interviews were analysed using Giorgi's phenomenological analysis. Results: Sixteen patients participated in the first interview and two patients completed follow-up interviews. Three themes were developed from the patients' interviews. (1) Exposure to witnessing resuscitation: patients who witness resuscitation felt exposed to a distressing event and not shielded by bed-space curtains, but after the resuscitation attempt, they also felt reassured and safe in witnessing staff's response. (2) Perceived emotional impact: patients perceived an emotional impact from witnessing resuscitation and responded with different coping mechanisms. (3) Patients' support needs: patients needed information about the resuscitation event and emotional reassurance from nursing staff to feel supported, but this was not consistently provided. Conclusion: The presence of other patients during resuscitation events must be acknowledged by healthcare professionals, and sufficient information and emotional support must be provided to patients witnessing such events. This study generates new evidence to improve patients' experience and healthcare professionals' support practices. Impact: The phenomenon of patient-witnessed resuscitation requires the attention of healthcare professionals, resuscitation officers and policymakers. Study findings indicate that witnessing resuscitation has an emotional impact on patients. Strategies to support them must be improved and integrated into the management of in-hospital resuscitation. These should include providing patients with comprehensive information and opportunities to speak about their experience; evacuating mobile patients when possible; and a dedicated nurse to look after patients witnessing resuscitation events.